Business strategy, distinctive capabilities, business environment and performance of manufacturing companies in Nigeria - Muhammed, Abdulrahman (2018)
Despite the contributions of manufacturing sector to economic and technological development of various countries, the sector is faced with many challenges leading to poor performance in many developing countries including Nigeria. Many factors are found to influence organizational performance of the sector. These include among others; poor electricity service, inadequate access to finance, competition from foreign goods and others. To address these challenges, strategic management academics and practitioners have conducted a lot of investigations focusing on business strategies, distinctive capabilities and organizational performance. However, it appears that very little empirical research efforts are available to address the issues in line with the peculiarity of the developing countries such as Nigeria. The objective of this study is to examine the relationships between business strategies, distinctive capabilities and performance of manufacturing companies with the moderating roles of electricity service and access to finance representing business environment. The study used adopted survey instruments to collect data from 309 selected manufacturing companies in Nigeria. Using SPSS 22.0, Multiple Regression and moderated analyses were employed to measure relationships between the predictor and criterion variables as well as determine the roles of the moderators. Results indicated that differentiation strategy, research and development capabilities and technological capabilities have significant positive relationships with organizational performance. Findings also revealed that both access to finance and reliability dimension of electricity service moderated only the marketing capabilities and organizational performance relationship. Whereas, responsiveness dimension of electricity service moderated marketing capabilities-performance relationship and technological capabilities performance relationship. These results imply that manufacturing companies need to pay attention to access to finance and electricity service quality while implementing strategies and capabilities. Apart from contributing to the existing literature, this study also extended Resource Based View by incorporating finance and electricity as situational factors.